2002
DOI: 10.1152/ajpregu.00260.2001
|View full text |Cite
|
Sign up to set email alerts
|

HPA-axis responses during experimental colitis in the rat

Abstract: We investigated the responses of the hypothalamic-pituitary-adrenal (HPA) axis during experimental colitis induced by intracolonic administration of 2,4,6-trinitrobenzenesulfonic acid in the rat. On days 3 and 7 after induction of colitis, the corticotropin-releasing hormone (CRH) mRNA level in the parvocellular paraventricular nucleus (pPVN) of the hypothalamus was reduced, the plasma ACTH level remained at the basal level, and the plasma corticosterone (Cort) level was high. Induction of colitis on day 3 aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 46 publications
(50 reference statements)
3
19
0
1
Order By: Relevance
“…The condition under which we have previously demonstrated enhanced weight loss in our P14 LPS-treated rats, experimental colitis, can be regarded as extremely stressful (28,53) and is representative only of individuals suffering from inflammatory bowel disease, a condition in which weight loss is evident regardless of neonatal experience (56). In the present study, we examined body weight under physiological conditions more likely to be experienced by the general population.…”
mentioning
confidence: 93%
“…The condition under which we have previously demonstrated enhanced weight loss in our P14 LPS-treated rats, experimental colitis, can be regarded as extremely stressful (28,53) and is representative only of individuals suffering from inflammatory bowel disease, a condition in which weight loss is evident regardless of neonatal experience (56). In the present study, we examined body weight under physiological conditions more likely to be experienced by the general population.…”
mentioning
confidence: 93%
“…It has become evident in recent years that the immune system is closely involved with stress-relieving mechanisms, in particular in relation to the nervous and endocrine systems. 4 In a study in rats, Kojima et al 5 showed that persistent infl ammatory stress from chronic colitis causes increased production of glucocorticoids, the fi nal product of the HPA-axis, and that these applied persistent negative feedback to the hypothalamus and pituitary glands. In a rat colitis model, Kresse et al 6 found that the HPAaxis is chronically activated, suggesting that overexpression of stress hormones upsets its functional balance.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that in physiological conditions the central CRH is regulated by the inhibitory feedback of cortisol that acts as a controlling factor of the inflammation. In rats, adrenalectomy and cortisol pellet replacement result in a marked increase in CRH mRNA, confirming the inhibitory feedback exerted by glucocorticoids in reaction to stress [62] . This study is supported by the results from Million et al [50] suggesting the protective role of CRH in stress-induced worsening of colitis.…”
Section: Hpa Responsementioning
confidence: 62%